Pemberdayaan Generasi Muda dengan Membangun Perencanaan Keuangan Melalui Investasi Berbasis Digital di Desa Siangan - Kadek Diviariesty; Ida Ayu Trisna Yudi Asri; I Gusti Agung Ayu Mas Suariedewi (Postgraduated Community Service Journal, 2023)
Partner in implementing Community Services is located in Siangan Village, Gianyar Regency. The targets of this Community services is the young generations who are members of youth organizations (Karang Taruna) in Siangan Village. The young generations (Karang Taruna) is the Millennial Generation and Generation Z, which are individuals born between 1981 and 2012, becoming very important groups in today's society. According to the Central Statistics Agency (BPS) census, the number of Millennial Generations in 2023 reached 47.3% and Generation Z will be around 60 million people from the total population in Indonesia. The background for implementing the activity is due to the lack of understanding of the younger generation regarding financial planning and investment. With rapid technological advances and social changes, this generation is faced with unique challenges in financial planning and investment. The aim of this activity is to provide understanding and knowledge regarding financial planning concepts and the types of investment instruments that are currently popular. The methods that are used in implementing this activity is the counseling and discussion method with a cooperative learning approach. It can be concluded that there is an increased in understanding, interest and ability by members of the Siangan Village Karang Taruna regarding financial planning through digital-based investments.